Alih Kode dan Campur Kode dalam Interaksi Pembelajaran Bahasa Inggris di Fakultas Pertanian Universitas Trunojoyo Madura - Eka Susylowati; Meria Zakiyah Alfisuma; M.Masqotul Imam Romdlani (Universitas Sebelas Maret, 2023)
The purpose of the research is to describe code choice and code mixing in the interaction of learning English in Agriculture Faculty University of Trunojoyo Madura. The reseach data included the code switching and code mixing of Agriculture students when learning English in the classroom. The data analysis use a contextual approach of Speaking by Dell Hymes. The result of the research showed that code switching used by the students in the Faculty of Agriculture, namely English and Indonesia, switching codes from English into Indonesia and vice versa, meanwhile code mixing from English into Inonesia, and mixed Indonesia into Javanese, mixed Javanese into English.